(untitled) (Pesquisa Odontológica Brasileira, 2001)
Staphylococcus aureus belongs to the normal flora of the skin, mucosa and nasopharynx of several animal species, including man, but it is also associated to illnesses such as abscesses, bacteremia, endocarditis and osteomyelitis, besides showing resistance to multiple drugs. The purpose of this paper was to evaluate the disinfecting ability of ozone when dissolved in water. Suspensions of Staphylococcus aureus with concentrations varying from 10(6) to 10(16) microorganisms/ml were prepared. One milliliter of each recently prepared suspension was added to 99 ml of distilled water (with or without previous ozonization) contained in a crystal reactor. Aliquots of 0.1 ml of this new suspension were taken at various time intervals and, then, serially diluted and inoculated on plaques. The data indicated that there was difference in the disinfecting effect when distilled water was used with and without previous ozonization.